2008
DOI: 10.1209/0295-5075/84/48001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curvature and topology on membrane hydrodynamics

Abstract: We study the mobility of extended objects (rods) on a spherical liquid-liquid interface to show how this quantity is modified in a striking manner by both the curvature and the topology of the interface. We present theoretical calculations and experimental measurements of the interfacial fluid velocity field around a moving rod bound to the crowded interface of a water-in-oil droplet. By using different droplet sizes, membrane viscosities, and rod lengths, we show that the viscosity mismatch between the interi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Membranes can be approximated as a viscous fluid enclosed by fluids on both sides. Recent studies have shown that hydrodynamics vary as a function of tubule geometry for membranes (Daniels and Turner, 2007; Henle and Levine, 2010; Henle et al. , 2007; Domanov et al.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes can be approximated as a viscous fluid enclosed by fluids on both sides. Recent studies have shown that hydrodynamics vary as a function of tubule geometry for membranes (Daniels and Turner, 2007; Henle and Levine, 2010; Henle et al. , 2007; Domanov et al.…”
Section: Discussionmentioning
confidence: 99%
“…An important empirical result of the calculation [25] is that the speed v 0 = |u m | of the membrane at the apex of the vesicle has a simple dependence on r ± ≡ η m /Rη ± , the non-dimensional form of the 'Saffman-Delbrück' lengths ± ≡ η m /η ± [1,31]: Rγ/v 0 = Ar + /r − +Br + +C , where A, B, C are known constants. When the inner and…”
Section: =∇π (1)mentioning
confidence: 99%
“…Here, we instead seek a classical hydrodynamic explanation for the additional drag, and hence reduced diffusion, of curvature-inducing proteins. In order to take account of the geometry of the membrane, we employ a covariant formulation of low Reynolds number hydrodynamics in two dimensions [7][8][9][10]. In doing so, we neglect both membrane fluctuations and any chemical interactions occurring between the protein and the amphiphilic molecules that make up the membrane [11,12].…”
mentioning
confidence: 99%